KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DENGAN MEMPERHATIKAN KEMAMPUAN AWAL DAN GAYA KOGNITIF - Suradi Suradi; Sahid Sahid (Universitas Negeri Makassar, 2017)
The aims of this qualitatively descriptive study are to describe the students’ capability in solving mathematics problems which focused on the initial capability and cognitive one. There are three instruments used in this research: (1) initial capability test, (2) GEFT test, and (3) Problem Solving Ability Test. The result of this research is students’ ability in problem solving bases on Polya Problem Solving Indicator: (1) understanding problems, (2) planning for solution (3) solving the problems, (4) recheck the result which has been gained